The lysosomal Ragulator complex plays an essential role in leukocyte trafficking by activating myosin II - Takeshi Nakatani (Nature Portfolio, 2021)
Myosin II–mediated contractility is required for leukocyte migration. Here, authors show that lysosomes are involved in leukocyte migration by providing the platform where Ragulator complex interacts with the myosin phosphatase Rho-interacting protein (MPRIP) independently of mTORC1 and interferes with the interaction between MPRIP and a subunit of myosin light chain phosphatase (MLCP).